PENGEMBANGAN DAN PEMANFAATAN MATA AIR YEH HA UNTUK SISTEM PENYEDIAAN AIR MINUM (SPAM) DI DESA SERAYA KABUPATEN KARANGASEM - Cahyadi, I Bagus Arya; Arsana, I.G.N. Kerta; Suryantara P., I Putu Gustave (Jurnal Ilmiah Teknik Sipil, 2016)
Seraya Village consist of West Seraya, Central Seraya and East Seraya. Central Seraya, East Seraya and Bunutan Village. They are well known as the village with lack of water supply. Therefore, a planning of water supply system is required to fulfill the optimum level of service. The planning of water distribution network is derived from Yeh Ha spring water, which is located in Abang District. Yeh Ha spring water is located in a high altitude (369 meter above sea level) so that gravity system is required in the planning of water distribution network. Based on data in RISPAM (Master Plan of Potable Water System) of Karangasem regency, Yeh Ha spring water capacity is about 330 liter/sec while the existing demand are used to irrigation system for 50 Ha irrigation area. Meanwhile, 20 liters/sec of amounted is used as drinking water. The analysis of drinking water demand to calculate reservoir capacity is between 15 – 20 % from maximum demand while the hydraulic analysis of transmission pipes is computed by Waternet software. Furthermore, water demand projection can be projected for 20 years ahead to determinethe capacity of water needs for three villages such as Seraya Tengah village, Seraya Timur Village and Bunutan village. Based on Waternet simulation program, the pipes system generated a huge relative energy which is reached 18 bar. Based on the result of relative energy, quality of the pipes can be defined. Water pipes system on the site plan is using galvanized iron, which has a diameter between 0.4 meters and 0.7 meters long and it is only used for the transmission pipe to reservoir. This pipeline network used gravity system only.
Keywords: Potable water , Waternet software, Water piped transmission.